Investigating critical organizational factors toward sustainability index: Insights from the Taiwanese electronics industry. (2nd August 2017) - Hsu, Chia‐Wei; Chang, Dong‐Shang
Abstract : To improve sustainable practices and attract investors, companies in emerging markets have increasingly embraced strategies for inclusion in rapidly expanding sustainability indices. However, most early studies on socially responsible investment or sustainability investment have only focused on exploring the relationship between corporate sustainability and firm value. Moreover, little has been done to explore the practices of emerging market companies for engaging with a sustainability index. To address this research gap, we employed the decision‐making trial and evaluation laboratory (DEMATEL) method to identify critical factors that influence the inclusion of emerging market companies in the Dow Jones Sustainability Index (DJSI). Five critical factors and best practices were identified based on the analysis of seven Taiwanese electronics companies that have been listed in the DJSI for several consecutive years. Our results provide insights on the critical factors and best practices that reinforce the sustainable practices of emerging market companies for inclusion in the DJSI. This study also contributes to the literature by investigating the engagement of emerging market companies with the DJSI.